2017
DOI: 10.1002/ece3.3263
|View full text |Cite
|
Sign up to set email alerts
|

The underestimated role of temperature–oxygen relationship in large‐scale studies on size‐to‐temperature response

Abstract: The observation that ectotherm size decreases with increasing temperature (temperature‐size rule; TSR) has been widely supported. This phenomenon intrigues researchers because neither its adaptive role nor the conditions under which it is realized are well defined. In light of recent theoretical and empirical studies, oxygen availability is an important candidate for understanding the adaptive role behind TSR. However, this hypothesis is still undervalued in TSR studies at the geographical level. We reanalyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 35 publications
(64 reference statements)
3
23
0
Order By: Relevance
“…Therefore, in our study system, salinity (indirectly) and pH (directly) affected the response 366 of size to temperature, causing the absence of the expected decrease with increasing temperature. 367 Intriguingly, under such conditions, the rotifer species exhibited smaller sizes at lower oxygen 368 levels, as predicted by the theory, confirming the crucial role of the oxygen concentration in 369 driving body size patterns (Walczyńska & Sobczyk, 2017). The only exception to the "when 370 there is less oxygen, grow smaller" rule was observed for the smallest species, B. rotundiformis.…”
supporting
confidence: 54%
See 1 more Smart Citation
“…Therefore, in our study system, salinity (indirectly) and pH (directly) affected the response 366 of size to temperature, causing the absence of the expected decrease with increasing temperature. 367 Intriguingly, under such conditions, the rotifer species exhibited smaller sizes at lower oxygen 368 levels, as predicted by the theory, confirming the crucial role of the oxygen concentration in 369 driving body size patterns (Walczyńska & Sobczyk, 2017). The only exception to the "when 370 there is less oxygen, grow smaller" rule was observed for the smallest species, B. rotundiformis.…”
supporting
confidence: 54%
“…The lack of a relationship between temperature and oxygen seems to be sufficient to 292 explain the lack of an influence of temperature or oxygen on rotifer body size that was found 293 when individuals of the different species were merged. The importance of the link between 294 temperature and the oxygen concentration in modulating species size was previously shown for 295 Icelandic diatoms (Walczyńska & Sobczyk, 2017). Sur.…”
mentioning
confidence: 79%
“…In support of a role of oxygen in setting body size limits, we previously showed that the TSR in a freshwater isopod crustacean was manifested most strongly under hypoxic conditions, whereas hyperoxia could reverse the TSR (Hoefnagel & Verberk, ). Recent studies have also highlighted the potential role of oxygen in setting body size limits (DeLong et al., ; van Rijn, Buba, DeLong, Kiflawi, & Belmaker, ; Walczyńska & Sobczyk, ) shifting the focus toward explanations for a TSR to asymptotic size. von Bertalanffy's model provides an explanation for smaller asymptotic size in warmer environments, but does not make explicit predictions about the effect of temperature on size at maturity.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for such fluctuation is that during summers (pre-monsoon), the river velocity, temperature, rainfall, and anthropogenic activities are higher as compared to post-monsoon. High temperature is inversely proportional to the dissolved oxygen (Connolly et al 2004;Buckup et al 2007;Walczyńska and Sobczyk 2017), which might results in a decrease in the diversity of macroinvertebrates in that region. The results correlate with the studies wherein the anthropogenic and other environmental factors are responsible for the statistically significant difference in macroinvertebrates assemblage seasonally (Kang and King 2013;Sartori et al 2014;Goswami and Singh 2017;Roy and Homechaudhuri 2017;Verdura et al 2019;Xue et al 2019).…”
Section: Change In the Diversity Of Macroinvertebrates In Response Tomentioning
confidence: 99%